Perjumpaan Gereja dan Budaya Lokal: Inkulturasi Liturgi Perkawinan dengan Gondang Sabangunan - Anri; Pereira, Alberto Alves (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2021)
In proclaiming Christ as the savior, the Church is in touch with the diversity of the local cultures. In the spirit of its founder, the Church becomes humble and is open to the dialog with the local cultural traditions, one of which in this article is the Toba Batak culture. This research aims to display the inculturation of marriage liturgy with the music of gondang sabangunan Batak Toba, particularly in the closing rite after the signing of marriage documents and during the procession of leaving the church in the Roman Catholic rite. This article makes use of the interview approach and the equivalence method. Through the inculturation of the marriage liturgy, the local church is in dialogue with the Toba Batak culture. It is an appropriate way for the Church to convey the Gospel message, by embracing elements that are unique and rich in the music of gondang sabangunan Batak Toba and relating them to the Christian teaching. The sacred values found in the musical of gondang sabangunan support the nobility and the dignity of a Catholic marriage. This inculturation can be seen as an encounter of Christ, the Church, and the local culture. While the process takes time, this exploration of an inculturation in liturgy can bring the faithful, especially the Batak Toba people, towards the experiences of repentance, holiness, and salvation.